2008
DOI: 10.1007/s00468-008-0225-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological variation in western redcedar (Thuja plicata) populations under contrasting soil water conditions

Abstract: Adaptation to precipitation conditions may induce genetic diversity that changes morphological and physiological traits. This hypothesis was investigated in the seedlings of seven western redcedar (Thuja plicata Donn ex D. Don) populations, which were collected along a precipitation transect from the Pacific coast to the southern interior of British Columbia, Canada. The experimental seedlings were either well-watered or soil-droughted and measured for growth, gas exchange rates, transpiration efficiency, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
3
19
0
1
Order By: Relevance
“…Fan et al (2008) observed that δ 13 C is highly dependant on the environmental conditions and obtained different rankings of redcedar populations under different environments and none relationship between WUE and origin of populations. There are also evidences of the contrary, δ 13 C decreased with summer dryness of the seed sources between ten Pinus contorta populations (Guy and Holowachuck, 2001).…”
Section: G × E Interactionmentioning
confidence: 98%
“…Fan et al (2008) observed that δ 13 C is highly dependant on the environmental conditions and obtained different rankings of redcedar populations under different environments and none relationship between WUE and origin of populations. There are also evidences of the contrary, δ 13 C decreased with summer dryness of the seed sources between ten Pinus contorta populations (Guy and Holowachuck, 2001).…”
Section: G × E Interactionmentioning
confidence: 98%
“…Thuja plicata is known to be extremely sensitive to water stress (Fan et al 2008), which is why we hypothesized that higher temperatures in urban areas would lead to decreased seedling recruitment and increased seedling mortality, as high temperatures generally increase water stress. However, we did not find lower seedling densities in urban forests compared to rural ones.…”
Section: Urbanization Impacts On T Plicata Recruitment and Growthmentioning
confidence: 99%
“…Although widely distributed in the region under sharply contrasting environmental conditions, western redcedar has been found to vary little genetically in isozymes (e.g., Yeh, 1988), while there is reported population variation in microsatellites (O'Connell et al, 2001). Significant family variation has been shown for western redcedar in growth rates (Russell et al, 2003;Wang and Russell, 2006) and population variation in physiological and morphological traits (Fan et al, 2008;Grossnickle et al, 2005;Rehfeldt, 1994). Some adaptive genetic variation is known to exist between western redcedar populations (Rehfeldt, 1994), though information on the amount and pattern of this variation in relation to precipitation gradients and soil water regimes is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…These seedlings were grown under a standard container-nursery cultural regime used in British Columbia, Canada (Van Eerden and Gates, 1990). All populations were grown as part of a homogeneous nursery crop population and had statistically similar height, diameter, shoot and root dry weight, before trial initiation (Fan et al, 2008).…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation